2020
DOI: 10.7759/cureus.12289
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant Staphylococcus aureus and Classical Enterotoxin Genes Among Sudanese Food Handlers

Abstract: Food handlers who carry enterotoxin-producing Staphylococcus aureus could become potential reservoirs of Staphylococcal food poisoning. The study is a cross-sectional one aimed to determine the prevalence of methicillin-resistant S. aureus (MRSA) and staphylococcal enterotoxins from randomly selected food handlers in Al Jazirah state, Sudan. Culture swabs were collected from the hands and nasals of food handlers (2016-2018). Identification of S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Nearly similar results were reported by (Bassyouni et al, 2012) who investigated S. aureus in 36.1% hand swabs of food handlers. While lower results were reported by (Castro et al, 2016;Beyene et al, 2019;Ahmed, 2020;Alves et al, 2021) in percentage of 11.1%, 11.3%, 25%, and 8.9%, respectively. These results revealed that food handlers play a great role in microbial contamination of food (Yap et al, 2019).…”
Section: Resultsmentioning
confidence: 58%
“…Nearly similar results were reported by (Bassyouni et al, 2012) who investigated S. aureus in 36.1% hand swabs of food handlers. While lower results were reported by (Castro et al, 2016;Beyene et al, 2019;Ahmed, 2020;Alves et al, 2021) in percentage of 11.1%, 11.3%, 25%, and 8.9%, respectively. These results revealed that food handlers play a great role in microbial contamination of food (Yap et al, 2019).…”
Section: Resultsmentioning
confidence: 58%
“…In this study, it was observed that S. aureus was isolated in half of the samples of nasal cavities and underside of nails from food handlers. According to Castro et al, 15 Ahmed, 25 and Saber et al 26 the presence of S. aureus in the hands and/or noses of food handlers was of 30%, 25%, and 30%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…This gene is commonly associated with contaminated food and is considered the enterotoxin gene most prevalent and leading cause of staphylococcal food poisoning worldwide. 15 , 25 , 27 , 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, since health professionals are in direct contact with patients who may be contaminated, non-compliance with hygiene rules can be a way of spreading MRSA inside and outside the hospital environment, and in the community [29]. As previously mentioned, S. aureus has the ability to colonize different areas of the human body, with a preference for the nasopharynx [30] and the ability to spread as well as being transmitted by direct contact (mainly by hands) or indirect (contaminated surfaces) [31][32][33]. Indeed, one of its fundamental biological characteristics is the ability to colonize the healthy population asymptomatically (asymptomatic carrier), thus assuming an important role in spreading to other areas of the body, to other people and even contaminating food and surfaces during handling [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, S. aureus has the ability to colonize different areas of the human body, with a preference for the nasopharynx [30] and the ability to spread as well as being transmitted by direct contact (mainly by hands) or indirect (contaminated surfaces) [31][32][33]. Indeed, one of its fundamental biological characteristics is the ability to colonize the healthy population asymptomatically (asymptomatic carrier), thus assuming an important role in spreading to other areas of the body, to other people and even contaminating food and surfaces during handling [31][32][33]. This colonization is considered a risk factor for the onset of infections by S. aureus, often combined with methicillin resistance-MRSA, increasing the risk of clinical disease [33,34].…”
Section: Discussionmentioning
confidence: 99%